The Juridical Implications of Acts of Default on Cooperation Financing Agreements Associated with Guarantees on Behalf of Third Parties - Arif, Cahyadhi (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
This study aims to find out and analyze the juridical implications of default on financing cooperation agreements associated with guarantees on behalf of third parties. To find out and analyze efforts to resolve defaults on financing cooperation agreements associated with guarantees on behalf of third parties. The research approach method used in this thesis is a sociological juridical legal research method. The specification of this research uses descriptive analysis. The type of data used in this research is primary data which includes Al-Quran, Hadith, UUD 1945, HIR, Civil Code, UU no. 2 of 2014 concerning Amendments to Act No. 30 of 2004 concerning the Office of a Notary Public, as well as secondary data containing books and other supporting documents. Collecting research data using interview techniques and study of documents or library materials. The data analysis method used in analyzing the data is qualitative analysis, such as description techniques, evaluation techniques and argumentation techniques. The results of the study show that private agreements on financing the construction of housing plots in the Bandung Regency area are very high risk, but can truly bind the parties and have legal certainty if they fulfill the requirements as stipulated in the Civil Code. Regarding the existence of a guarantee on behalf of a third party in an agreement that is not bound by itself, even if there is a power of attorney to sell made by an authorized official on behalf of the owner of the guarantee to the recipient of the capital, it does not have any strength or value whatsoever.Keywords: Agreements; Guarantees; Financing.